การผลิตอาหารเสริมสุขภาพเพื่อป้องกันโรคข้อกระดูกเสื่อมจากเปลือกอาหารทะเล : รายงานการวิจัย - มงคล สุขวัฒนาสินิทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The degradation of squid pen by using enzymes of aspergillus fumigatus and coned bacteria serratia sp. can be accomplished to specifically N-acetyl-D-glucosamine (GIcNAc) and NN-acetylchitobiose [(GIcNAc)2]. Enzyme of aspergillus fumigatus (4 U/1 g of chitin) can degrade chitin (3% w/v) at 40 ํC, pH 3, for 2 days, to give GlcNAc in 72% yield. The degradation of chitin (3% w/v) by using enzymes from bacteria serratia sp (1 U/1 g of chitin) at 37 ํC, pH 6, for 6 days, to produce both (GIcNAc)2 and GIcNAc in 72% and 2.6% yields respectively. The purification of GIcNAc and (GIcNAc)2 could be done by recrystallization following by either the activated charcoal decolorization or the activated charcoal column chromatography to obtain pure GIcNAc in 64% yield and pure (GIcNAc)2 and 40% yield. The degradation of chitin by using conc. HCI to obtain glucosamine hydrochloride salt (GIcNHCI) can be accomplished with or without ultrasonication. The conditions is to use chitin to conc. HCI ratio 1:1 (w/w) and the degradation by using conc. HCI is under investigation.